ANALISIS STRATEGI PENGEMBANGAN BISNIS PT PERUSAHAAN GAS NEGARA (Studi pada PGN Sales Area Semarang) - Amalia Putri Pertiwi; Sudharto Prawata Hadi (Universitas Diponegoro, 2020)
The use of gas for the domestic sector especially in Java island, is the largest consumer center in Indonesia. Natural gas providers face the main challenge of providing adequate supplies to meet the increasing demand. The BUMN company that sells and distributes its products in the form of natural gas in Central Java is the PGN Semarang sales area. As a company engaged in the service sector, a good strategy is needed so that the company can carry out all operational activities more efficient and effective.This study aims to analyze the National Gas Company business strategy (study at the Semarang PGN sales area). The type of research is qualitative descriptive analysis. The data collection technique by interviewing interviewees and direct observation. The number of speakers is 4 speakers, who are Head area and employees of the Semarang PGN sales area who are also the strategists. The results showed that the strategy developed by PGN Sales Area Semarang was the result of a SWOT Analysis based on alternative strategis. The implementation of the strategy implemented and obtained from the SWOT results has been effective because it is in accordance with the vision, the availability of HR (Human Resources), facilities and infrastructure that support PGN. Although there are several obstacles in implementing its strategy, PGN Sales Area Semarang is committed to continue to improve the implementation of its strategy in the distribution of natural gas in Semarang.Suggestions for this research are the addition of CNG fleet in meeting natural gas needs, increase distribution of gas sales due to gas supply continuity, increase and improve the size for the effectiveness of strategy implementation, socializing the use of BBG to the public, provide excellent service to customers, doing routine monitoring and evaluation related to ths implementation of PGN's business development strategy.